2021
DOI: 10.1177/13623613211051150
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of a virtual nutrition intervention for adolescents with autism spectrum disorder

Abstract: Adolescents with autism spectrum disorder are at increased risk of unhealthy eating behaviors and obesity. This study examined feasibility of a virtual implementation of Bringing Adolescent Learners with Autism Nutrition and Culinary Education, an 8-week nutrition intervention based on social cognitive theory that addresses autism spectrum disorder–specific eating behaviors and food environment challenges. The implementation process was measured with fidelity checklists, engagement records, and field notes. Fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 46 publications
1
15
0
Order By: Relevance
“…Although participants were not asked specifically about SCT constructs, adolescents and parents mentioned knowledge/awareness, behavioral strategies, self-efficacy, outcome expectations, and outcome expectancies. These qualitative findings confirmed the significant pre-/post-intervention mean differences detected for behavioral strategies ( p = 0.010), self-efficacy ( p < 0.001), and outcome expectations ( p = 0.009) in our quantitative assessment (Buro et al, 2021 ) and indicated that BALANCE shows promise at improving some psychosocial determinants of dietary intake. These results are also consistent with findings of the other recent virtual nutrition education intervention for adolescents with ASD; parents reported via close-ended survey responses that the intervention improved their children’s knowledge and eating habits (Shurack et al, 2021 ).…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…Although participants were not asked specifically about SCT constructs, adolescents and parents mentioned knowledge/awareness, behavioral strategies, self-efficacy, outcome expectations, and outcome expectancies. These qualitative findings confirmed the significant pre-/post-intervention mean differences detected for behavioral strategies ( p = 0.010), self-efficacy ( p < 0.001), and outcome expectations ( p = 0.009) in our quantitative assessment (Buro et al, 2021 ) and indicated that BALANCE shows promise at improving some psychosocial determinants of dietary intake. These results are also consistent with findings of the other recent virtual nutrition education intervention for adolescents with ASD; parents reported via close-ended survey responses that the intervention improved their children’s knowledge and eating habits (Shurack et al, 2021 ).…”
Section: Discussionsupporting
confidence: 82%
“…The conceptual framework for BALANCE (Buro et al, 2021 ) incorporates SCT constructs and ASD-specific challenges, including sensory differences (Hazen et al, 2014 ) and cognitive rigidity (Polfuss et al, 2016 ), to promote positive dietary behavior change. The virtual implementation included eight weekly 30–45-min lessons delivered via Microsoft Teams (exploring taste, flavor, and texture; mealtimes and rules; food groups and nutrients; moderation; beverages; cooking; well-being; and sustaining healthy eating habits), as well as weekly homework assignments, weekly parent email handouts, and three parent webinars.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Teams intervention consisted of eight weekly lessons that were initiated within an in-person setting and adapted for virtual implementation via Microsoft Teams ( n = 27, with six groups of 2–7 adolescents aged 12–21 years) ( Buro et al, 2021 ). Sensory activities including food tasting and preparation and visual and verbal prompts in the form of lesson booklets to reference during and between lessons and printed activity cards were utilized to engage participants.…”
Section: Discussionmentioning
confidence: 99%
“…The current report describes the development, implementation, and evaluation of two novel virtual nutrition education interventions for adolescents with ASD ( Buro et al, 2021 ; Shurack et al, 2021 ). The authors of both studies documented the feasibility and acceptability of the two virtual pilot programs.…”
mentioning
confidence: 99%